In vitro effect of slkaloids on bloodstream forms of Trypanosoma brucei and T. congolense - Merschjohann, Karin; Sporer, Frank; Steverding, Dietmar; Wink, Michael (Planta medica, 2001)
Thieme E-Books & E-Journals
Gesehen am 06.10.2017